Prognostic value of the neutrophil-to-lymphocyte ratio and prognostic nutritional index in unresectable hepatocellular carcinoma patients treated with tyrosine kinase inhibitors and immune checkpoint inhibitors - Shasha Sun; Wendong Li; Xiaodi Guo; Jinglong Chen (Human Vaccines & Immunotherapeutics)
This study aimed to investigate the role of the neutrophil-to-lymphocyte ratio (NLR) and prognostic nutritional index (PNI) in unresectable hepatocellular carcinoma (HCC) patients treated with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs). The optical cutoff values of the NLR and PNI were determined via time-dependent receiver operating characteristic curve analysis. The associations between overall survival (OS) and various potential risk factors were analyzed. Forty-nine HCC patients were enrolled in this retrospective study. The optimal pretreatment NLR and PNI cutoff values were 2.4 and 41, respectively. The median follow-up was 8 (range 3–36) months. The median OS in the high NLR subgroup was lower than that in the low NLR subgroup (7 vs. 9 months, p < .05). However, the high PNI group had better OS than the low PNI group did (12 vs. 7 months, p < .05). Univariate analysis revealed that tumor distribution (p = .003), PNI < 41 (p = .013), and NLR ≥ 2.4 (p = .010) were associated with unfavorable OS in HCC patients. The multivariate analysis revealed that the PNI (HR = 0.353, 95% CI 0.150–0.831; p = .017) and tumor distribution (HR = 0.336, 95% CI 0.137–0.826; p = .017) were independent indicators of poor prognosis. A pretreatment NLR ≥ 2.4 and PNI < 41 are related to poor survival in unresectable HCC patients receiving TKI and ICI treatment. Moreover, a lower PNI is an independent indicator of poor prognosis when ICIs are combined with TKIs.